Preadaptation, Firm Heterogeneity, and Technological Performance: A Study on the Evolution of Fiber Optics, 1970–1995 - Cattani, Gino (Organization Science, 2005)
Strategy research typically traces stable performance differences among firms to a priori heterogeneity in initial resource endowments or in expected flows of resources. The objective of this paper is to explore how this heterogeneity is created and how it affects firm technological performance. Within the framework of an evolutionary view of technological change, we develop the notion of technological preadaptation to describe that part of a firm’s prior experience that is accumulated without anticipation of subsequent uses. In particular, we hypothesize that (technological) performance differences are positively related to (1) firms’ stock of relevant skills and knowledge potentially available for applications other than those for which they were originally developed and (2) the extent to which firms actually build on these skills and knowledge in new domains. The empirical setting is fiber optics technology as it evolved for use in long-distance communications between 1970 and 1995. We find that “preadapted” firms that consistently leveraged their prior experience achieved higher levels of performance than did firms that did not leverage that experience or did not have prior experience. The study illustrates the importance of preadaptation in capability development and technological competition.